MAKTAB YOSHIDAGI O‘ZBEKZABON BOLALAR OG‘ZAKI NUTQINI MAIN METODOLOGIYASI ASOSIDA O‘RGANISH - Hamidova Gulrux Axmat qizi (TADQIQOTLAR, 2026)
Annotation. This article presents the experience of studying the oral narrative speech of school-aged (grades 1–5) Uzbek-speaking children based on the internationally standardized MAIN (Multilingual Assessment Instrument for Narratives) methodology. In the study, the speech of 11 participants was collected using the "Cat Story" visual stimulus and analyzed according to psycholinguistic indicators (MLU, TTR, syntactic complexity, speech rate). The article focuses on the methodological aspects of applying the MAIN instrument to the Uzbek language.